Choreography of Turonggo Seto Tunggal Wulung Dance by Eko Wahyu Prihantoro - Soryanto, Danang; Lestari, Wahyu (Jurnal Seni Tari, 2024)
Turonggo Seto Tunggul Wulung dance choreography adapts the story of Prince Diponegoro's struggle against the invaders. The choreography of the Turonggo Seto Tunggul Wulung dance by Eko Wahyu Prihantoro is a creative dance. The research aims to explore the choreography in the Turonggo Seto Tunggul Wulung Dance and find the supporting factors for the choreography and the factors inhibiting the choreography. The research method used is a qualitative method with a choreographic approach. Data collection techniques were carried out using interviews, observation, and documentation. In addition, the data validity technique is carried out by source triangulation. Data analysis techniques use data reduction, data presentation, and conclusions. The research results of the Turonggo Seto Tungul Wulung Dance Choreography had the idea from the folklore of the people on the slopes of Mount Merapi and Merbabu which interpreted the spirit of cooperation and tenacity of the community and as a form of Prince Diponegoro's struggle against the invaders. Exploration and movement vocabulary are based on the spirit of the community and are reflected in Prince Diponegoro's horse riding skills. Work on music using original musical works for the Turonggo Seto Tungul Wulung dance choreography composed by Jungkung Darmoyo. The supporting factor lies in the management system and the choreographer's ability in the choreography process. The inhibiting factor lies in the dancer's ability, but the choreographer has a concept to anticipate the lack of the dancer's ability.